Estimating the Gerber-Shiu Function in a Compound Poisson Risk Model with Stochastic Premium Income - Yunyun Wang; Wenguang Yu; Yujuan Huang (Discrete Dynamics in Nature and Society)
In this paper, we consider the compound Poisson risk model with stochastic premium income. We propose a new estimation of Gerber-Shiu function by an efficient method: Fourier-cosine series expansion. We show that the estimator is easily computed and has a fast convergence rate. Some simulation examples are illustrated to show that the estimation has a good performance when the sample size is finite.